EFEKTIVITAS PERAN PEMERINTAH DESA DALAM MENGATASI PERMASALAHAN KEGIATAN PERTAMBANGAN EMAS TANPA IZIN (PETI) DI DUSUN SUNGAI BULUH KABUPATEN BUNGO - Dina Sviyani; Indra Rahmat, Budi Juliardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the village government's role in addressing the problem of Illegal Gold Mining (PETI) in Sungai Buluh Hamlet, Bungo Regency. The PETI phenomenon has had negative impacts on the environment and society, making the active role of the village government crucial. Based on the research results, the role of the village government is divided into two main forms: prevention and enforcement. Prevention includes socialization, education, and warnings to the community about the dangers of PETI. Meanwhile, enforcement is carried out through coordination with security forces, conducting raids, and monitoring PETI locations. However, the effectiveness of this role faces obstacles, both internally in the form of differences in perception between the village government and the mining community, and externally such as low legal awareness and limited economic alternatives for the community. These findings indicate that handling PETI requires a more comprehensive approach, including strengthening regulations, economic empowerment, and synergy between government institutions. This research is relevant to the theory of social roles (Soejono Soekanto) and public policy (James E. Anderson), and is supported by legal provisions such as Law No. 4 of 2009 concerning Mineral and Coal Mining. Keywords: Village Government, PETI, Illegal Mining, Public Policy, Sungai Buluh Hamlet